Pengaruh Kualitas Produk, Persepsi Harga, Desain Interior terhadap Kepuasan Konsumen di Wizzmie - Milanisti, Dennisa Septiani; Muzakir , Muzakir; Ponirin , Ponirin; Asriadi , Asriadi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aimed to investigate the impact of product quality, perceived price, and interior design on customer satisfaction. In addition, this study aims to contribute to improving customer satisfaction in the restaurant sector. Research methodology: This study applied quantitative methods with non-probability purposive sampling technique. The sample consisted of 80 respondents. Data were obtained through a questionnaire using a Likert scale. Data analysis was conducted using SPSS version 30. Results: The results indicate that product quality, price perception, and interior design simultaneously influence customer satisfaction. Product quality has a positive and significant effect on customer satisfaction, as well as price perceptions and interior design which also show a positive and significant effect on customer satisfaction. Conclusion: This study concludes that product quality, perceived price, and interior design significantly enhance customer satisfaction in the restaurant industry. Product quality has the strongest impact, whereas fair pricing and appealing interior design further strengthen loyalty, making these three factors essential for building sustainable competitiveness. Limitations: This study has several limitations, including the object of research, which only includes Wizzmie consumers in Palu; therefore, the results cannot be generally applied to all Wizzmie branches in other areas. In addition, this study only focused on three variables, namely product quality, price perception, and interior design, without considering other factors that may also affect customer satisfaction. Contribution: The findings of this study can be utilized by the management of Wizzmie Palu and other culinary businesses as a basis for improving service quality and marketing strategies.